A preliminary study on lightweight concrete made from polystyrene waste - Mohd Syukri Mohd Mokhtar
This paper discusses the experimental study on the substitution of conventional aggregate made of crushed stone with modified polystyrene waste aggregate to produce lightweight concrete.